Notary Authority In Establishment Of Limited Liability Company (PT) In The Online Single Submission In Pekalongan City - Fathiyya Haura Geviana; Yusuf Abdurrohman (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: (1) identify and analyze the authority of the Notary in the establishment of a Limited Liability Company (PT) in the system Online Single Submission (OSS), (2) To overcome the barriers and solutions within the competence of notaries in the establishment of a Limited Liability Company (PT) in the system online Single Submission (OSS). The method used in this study is a sociological juridical research, specification used in this research is descriptive analysis, which analyzes the problem using the theory of legal certainty and the theory of expediency.Based on the research results can be concluded that in the establishment of Limited Liability Notary actual authority to do before the establishment however, Notary actual authority to do before, during and after the Company was established. Mechanisms to establish a business in the Online Single Submission system (OSS) for a limited liability company (PT). The first step to be able to apply for a business license through the OSS is a deed of establishment of PT and obtain ratification decree. Deed numbers and numbers ratification decree issued by the Directorate General of General Legal Administration (AHU) Kemenkumham will be entered into the OSS system. The process of filling the deed numbers and SK only when the data PT of AHU yet connected. This may happen given the current process of migrating data from the Directorate General of AHU to OSS is still ongoing. If the migration process is 100% complete, then manually enter no longer need to be done.Keywords: Notary Authority; Limited Liability Company; Online Single Submission (OSS)